Антропоморфна когнітивна модель порівняння. - Коропатніцька, Тетяна Петрівна (Вчені записки ТНУ імені В. І. Вернадського. Серія «Філологія. Журналістика». Київ: Видавничий двір «Гельветика», 2020)
The article focuses on the analysis of linguocognitive characteristics of comparative constructs with “wie” and “als” in modern German, conceptual space of referents and correlates where it brings together information about a person. Special features of the structure of the anthropomorphic cognitive model of comparison are being considered here. The analysis was performed using a method that contains such steps as selecting the material of the study using corpus analysis and through writing down method; frame modeling using matrix and network models for structuring and organizing the information. An attempt is made to present the comparison as a linguocognitive model of knowledge, as a process of understanding one concept or domain in terms of another, where hierarchical order appears as a concept → plot (set of concepts) → domain (set of plots). As a result of the analysis of comparative constructs with “wie” and “als”, the conceptual space of referents and correlates where it brings together information about a person, his physical and spiritual characteristics, appearance, feelings and mood, state, features of personality, thoughts and words, place in society, interpersonal relationships, etc., grouped into 4 domains: (1) HUMAN – SOCIAL BEING; (2) HUMAN – PHYSICAL BEING; (3) HUMAN – EMOTIONAL BEING; (4) HUMAN – SAPIENT BEING. It is considered that as a result of the interaction of the “MENSCH” reference concept and the “MENSCH” correlative domain, the reference concepts correlate with different correlative domain concepts. When mapping the MENSCH correlation al domain to the MENSCH reference concept, an anthropomorphic model of comparison is formed, which, as a result of the analysis of their conceptual space, is grouped into four cognitive anthropomorphic submodels of comparison: MENSCH ≡ GESELLSCHAFTLICHE NATUR, MENSCH ≡ ORGANISMUS, MENSCH ≡ PSYCHISCHES LEBEN, MENSCH ≡ TÄTIGKEITSBEREICHE, where a person is being compared with him- or herself, probably, because he/she intuitively perceives his/her personality and the society, where he/she lives in, as one. The comparative potential of the MENSCH (HUMAN) domains and of the anthropomorphic cognitive model of comparison, compared to other correlative domains was defined.
Keywords: comparative structures, reference domain, correlative domain, natomorphic cognitive model of comparison